Improving high-temperature mechanical properties of cast CrFeCoNi high-entropy alloy by highly thermostable in-situ precipitated carbides. (10th May 2021) - Liu, X.W.; Gao, N.; Zheng, J.; Wu, Y.; Zhao, Y.Y.; Chen, Q.; Zhou, W.; Pu, S.Z.; Jiang, W.M.; Fan, Z.T.
Highlights: Nb and C alloying results in carbide precipitation and significant high-temperature strengthening. Coarse grains and carbide pinning lead to highly microstructural thermostability. NbC particles with a high thermostability generate remarkable hardening. Abstract: The CrFeCoNi high-entropy alloy (HEA) exhibits excellent mechanical properties at lower temperatures due to its low stacking-fault energy, however, its medium- and high-temperature strengths are still insufficient. In consideration of the potential diversified applications, more strengthening approaches except for the previously proposed L12 phase hardening deserve further exploration due to its rapid coarsening tendency at high temperatures. Here, we achieved significant high-temperature strengthening of the cast CrFeCoNi HEA by in-situ precipitation of highly thermostable carbides. Alloys with 0.5 at.% and 1 at.% niobium and carbon were prepared by simple casting processes, i.e. drop cast, solute solution and aging. A highly thermostable microstructure was formed, which comprises very coarse grains accompanied with extensive thermostable carbide precipitates embedded, including submicrometer coherent NbC particles in grain interiors and intergranular coherent M23 C6 carbides. This high thermostability of microstructure, which is beneficial for the high-temperature loading, is ascribed to the synergy of lacking growth driving force and Zenner pinning effect by the carbides. Tensile properties tested at 673, 873 and 1073 K show that the yield strength and ultimate tensile strength are significantly increased by Nb/C doping, along with the elongation escalation at higher temperatures. The strengthening is mainly due to the precipitation hardening of carbide particles.